Colombia : Financial System Stability Assessment Update. (IMF Staff Country Reports; Country Report ;, 2005)
This paper presents a Financial System Stability Assessment Update, including Reports on the Observance of Standards and Codes (ROSC) on the Securities Regulation, Insolvency and Creditor Rights Systems, and Payment Systems in Colombia. Overall, the financial sector appears relatively stable and resilient to potential adverse shocks. The Superintendency of Banks lacks sufficient autonomy and independence while the current legal framework fails to effectively protect either bank supervisors or the Superintendent. Risk-based regulation and consolidated supervision remain key issues for the future.